Variables of Learning Environment and Aggressive Behaviours Among Secondary School Students in Katsina State, North Western Nigeria. - Dr Abdu Usman; Sunday Bassey Akpan; Samuel Benjamin Agerewe (Researchparks Publishing, 2023)
This study determined the influence of learning language of communication, over-crowded classrooms and social amenities on aggressive behaviours among Secondary School Students in Katsina State, North Western Nigeria. The population of the study comprised of 18,496 Senior Secondary II Students from the selected Public Secondary Schools across the three Senatorial Districts of Katsina State. Sample of 720 Students were drawn for the study using simple random sampling technique. The three (3) parts researchers’ made instrument entitled “Variables of Learning Environment and Aggressive Behaviours Among Secondary School Students Questionnaire (VLEABASSSQ)” was used for data collection. The instrument has been validated by three (3) independent experts, two (2) from Educational Psychology and one (1) from Federal University Dutsima, Test and Measurement Department. Cronbach’s Alpha reliability technique was used to determine the internal consistency of the instrument. The reliability co-efficient of 0.82 was obtained. The three (3) research questions raised in the study were answered using Mean and Standard Deviation while the null hypotheses were tested using Chi-square (X2) test. The results showed that the influence of learning language of communication, over-crowded classrooms and social amenities were significant. Therefore, all the null hypotheses were rejected. However, it was concluded that all the variables significantly influenced the aggressive behaviours among Secondary School Students in Katsina State, North Western Nigeria. The researchers recommended among other things that the School authority should impose stiffer sentences on students who exhibit aggressive behaviours and violate rules and regulations of the schools. In doing so, this serves as the most effective deterrent to others to refrain from such acts.